«Digo carne»: La repolitización del cuerpo femenino en la narrativa de Marta Sanz - Martín Huertas, Concepción (Studia Romanica Posnaniensia, 2020)
With the start of the new century, and especially during the last decade, many writers are starting to putt he focus on the body and its various problems derived from the current socioeconomic system. One of them is Marta Sanz, for whom, in her own words, writing consists of “naming the body” and, thanks to that, “conquering the territory”. His discourse is frontally opposed to the discourse of postmodernity and to the models of advanced capitalism, above all and more consciously in his latest novels. What this article aims to show is how and in what way the body and its repolitization constitute one of the central axes of this author’s writing.